EFEKTIVITAS PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMA NEGERI 1 ANGKOLA SELATAN - Miftahul Khoiriyah Batubara (JURNAL MathEdu (Mathematic Education Journal), 2018)
This study aims to describe the effectiveness of RME approach on students’ mathematical problem solving ability at the eleventh grade students of SMA Negeri 7 Padangsidimpuan. The research was conducted by using experimental (pretest post test one group design) method with 32 students as the sample and they were taken by using cluster random sampling technique from 98 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of RME approach was 3.46 (good category) and b) the average of students’ mathematical problem solving ability before RME approach was 66.50 (enough category) and after RME approach was 86.56 (very good category). Furthermore by using inferential statistic (Pair Sample ttest), it could be found significant value was less than 0.05 (0.000 <0.05). It means, RME approach is effective on students’ mathematical reasoning ability at the eleventh grade students of SMA Negeri 1 Angkola Selatan.